IDENTIFICATION OF GROUNDWATER DISTRIBUTION USING SELF POTENTIAL METHOD - Hasan, Muhammad Fathur Rouf; Swastika, Tri Widya; Martina, Nunung; Wulandari, Linda Sari (POLITEKNIK NEGERI JAKARTA, 2019)
Drought is one of the biggest problems for the community, this problem will be slightly resolved by the compilation of regions with groundwater sources. This research has been carried out in the karst area, Druju Village, Sumbermanjing District, Wetan Regency, Malang. The purpose of this study is to determine the distribution of underground air and the pattern between underground rivers in the Wonorejo draw well and spring sources in the Kaligoro River, Wonorejo Hamlet.The method that used is the Self Potential (SP) method to set the moving electrode (leap frop) with 104 measurement points. The results of this study indicate the value of electric potential shown between 0-13.5 mV, and assume that a low potential value (0-1 mV) is an indication of groundwater distribution. Areas with low potential values are found in the empathy area. When taking a distribution of water on the surface of the land that appears through the Kaligoro River, it does not need to go out in one stream with an underground river flowing in the wells of the residents. The area with the lowest potential value is a reference in making wells